Organizational and Management System of Provincial, District (City) Administrations - Yokubov, T. (European Journal of Life Safety and Stability (2660-9630), 2022)
Since the establishment of the Hokimist Institute in Uzbekistan, several changes, additions and corrections have been made to the organizational structure of regional, district (city) hokimities. During the transition of administrative reforms to the initial, middle and subsequent stages, some of them will end their life if one or another structure is needed. Therefore, there is a need to change the organizational structure of the administration.